Dynamic Coronary Roadmap for Contrast, and Radiation Time Reduction during Coronary Intervention (DRM-COR) - Maher, Mamdouh; Zarif, Bassem; Elgamal, Aya; Khairy, Hatem; Magdy, Ahmed (American Journal of Health, Medicine and Nursing Practice, 2022)
Purpose: The regularly used contrast media in the angiography procedures and interventions are known to carry certain risks to the patient. This includes allergy, nephrotoxicity, and pulmonary edema. Additionally, radiation exposure is associated with high bone marrow depression, infertility, and other hazards. The purpose of the study was to compare the Dynamic Roadmap technology to the regular contrast used in coronary intervention regarding radiation exposure, fluoroscopy time, and incidence of Contrast Induced Nephropathy. Methodology: Observational prospective cohort with 2 arms where 40 patients were randomly divided into 2 arms a case and control groups. The case group had DRM technology used in their procedures where the control group received the standard contrast used in the National Heart Institute. Findings: Findings showed no statistically significant difference between the 2 groups in age, sex, and risk profile including status of Hypertension, Diabetes Mellitus, Smoking and history of Ischemic Heart Disease. There was no difference in echocardiographic findings of both groups. There was significant difference in creatinine level at the 5th day of intervention and volume of contrast used and fluoroscopy time. DRM reduced contrast volume, reduced radiation exposure despite not reducing fluoroscopy or procedure time. This resulted in reduction of elevation in serum creatinine levels with similar success rates. Recommendations: Using the least possible contrast volume and radiation doses should always be target of the operator. Dynamic roadmap technology is recommended in all coronary interventions specially those at high risk of CIN with CKD.